A pilot study to survey the carnivore community in the hyper-arid environment of South Sinai Mountains - Gecchele, Lisa V.; Bremner-Harrison, Samantha; Gilbert, Francis; Soultan, Alaa Eldin; Davison, Angus; Durrant, Kate L. (Elsevier, 2017)
Carnivores are one of the taxa most affected by habitat fragmentation and human persecution; as a result, most carnivore species are declining; for this reason monitoring changes in carnivore population is paramount to plan effective conservation programs. Despite being one of the most threatened habitat, arid environment are often neglected and the carnivore species living in this environment are generally poorly studied. We conducted a pilot study to survey the carnivore guild in the St Katherine Protectorate, the largest Egyptian national park and a hotspot for biodiversity and conservation in an arid environments. Three species were detected using both camera trapping and morphological identification of scats: Red fox, Striped hyena and Arabian wolf, while through genetic analysis we were able to confirm the presence of Blandford fox as well. Arabian wolf appeared to be the most elusive and rarer species and should be a conservation priority.